2017
DOI: 10.1002/ajoc.201700156
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Sensing of Specific Drugs at Sub‐Ppb Levels by Using a Hybrid Organic–Inorganic Photoluminescent Soft Material

Abstract: The intrinsic luminescence of Tb III in ac holate (Ch) hydrogel has been found to be much higher than that in water or SDS micellar media. We have examined the role of the gel medium in enhancing the emission of Tb III in detail, and we also report ar emarkably simple methodf or detecting two important drugs,n aproxen andp ropranolol, by using the luminescence of Tb III in aT bCh hydrogel. The gel medium played ac rucial role in the sensing of these drugs, because little sensitization of Tb III took place in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…used a DHN‐doped Tb‐deoxycholate gel whose luminescence was quenched upon the addition of the electron deficient analyte, 2,4,7‐trinitrofluorenone, leading to its easy and rapid detection [39] . It is important to note that the efficient sensitization of the lanthanides necessarily requires the gel medium since the sensitization is negligible in the solution phase [40] . There are multiple reasons for the absolute need of the gel medium for sensing purposes using the lanthanide luminescence.…”
Section: Photoluminescent Hydrogels As Sensorsmentioning
confidence: 99%
“…used a DHN‐doped Tb‐deoxycholate gel whose luminescence was quenched upon the addition of the electron deficient analyte, 2,4,7‐trinitrofluorenone, leading to its easy and rapid detection [39] . It is important to note that the efficient sensitization of the lanthanides necessarily requires the gel medium since the sensitization is negligible in the solution phase [40] . There are multiple reasons for the absolute need of the gel medium for sensing purposes using the lanthanide luminescence.…”
Section: Photoluminescent Hydrogels As Sensorsmentioning
confidence: 99%
“…In the recent years, we have extensively worked on photoluminescent lanthanide cholate hydrogels [40,41] . We have shown the potential applications of these hydrogels for enzyme assays, [42,43] generating color‐tunable photoluminescent gels and xerogels including white light emitting gels, [40] for the synthesis of LnF 3 nanoparticles [44] and sensing naphthalene based drugs [45] . Recently, we also demonstrated a low‐cost, paper‐based approach for assaying various biologically important hydrolases [43,46] …”
Section: Figurementioning
confidence: 99%
“…[40,41] We have shown the potential applications of these hydrogels for enzyme assays, [42,43] generating color-tunable photoluminescent gels and xerogels including white light emitting gels, [40] for the synthesis of LnF 3 nanoparticles [44] and sensing naphthalene based drugs. [45] Recently, we also demonstrated a low-cost, paper-based approach for assaying various biologically important hydrolases. [43,46] In this work, we observed that a Tb cholate (TbCh) gel doped with GA or its derivatives EGCG or ECG showed green luminescence under 365 nm UV lamp (Figure 1a).…”
mentioning
confidence: 99%
“…[32] Over a century ago, Schryver reported the first metal cholate hydrogel, viz, calcium cholate (CaCh) gel, [33] but further exploration has been done only from 2009, and now several other metal cholate gels and their applications have been reported. [34][35][36][37][38][39][40][41][42] While a number of metal ions form gels with cholate, we chose calcium and europium cholates (CaCh & EuCh) for detailed studies. CaCh was selected as it showed a clear transition from a transparent sol to a gel ( Figure 1a) slowly (~3 h/25°C), giving sufficient time for kinetic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Over a century ago, Schryver reported the first metal cholate hydrogel, viz, calcium cholate (CaCh) gel, but further exploration has been done only from 2009, and now several other metal cholate gels and their applications have been reported . While a number of metal ions form gels with cholate, we chose calcium and europium cholates (CaCh & EuCh) for detailed studies.…”
Section: Introductionmentioning
confidence: 99%